tem cells in treating patients with coronary heart disease. Part II. Bone marrow-derived mononuclear cells - N. S. Zhukova; I. I. Staroverov (Кардиоваскулярная терапия и профилактика)
Cell cardiomyoplasty is a relatively new approach to restoring cardiac function after myocardial infarction (MI). Experimental and first clinical studies on stem cell (SC) transplantation in patients with acute MI and heart failure have demonstrated the improved myocardial perfusion and myocardial contractility, due to angiogenesis, reduced cardiomyocyte (CMC) apoptosis, and regressed left ventricular remodelling. However, despite these promising results, there are some barriers for a wider use of SC in treating cardiovascular patients. Multiple key aspects are yet to be clarified in future studies, including the mechanisms of transplanted SC homing, differentiation, and engraftment, the mechanisms of transplanted cell effects on cardiac function, etc. Such issues as the preferential source for SC transplantation in clinical settings, the method of cell transport into myocardium, the optimal cardiomyoplasty time, the number of the transplanted cells and the methods for their pre-transplantation processing are still under discussion. The second part of the present review describes the bone-derived mononuclear cells, as the cell fraction which is widely used in the clinical studies on SC and myocardial injury. Some problems and safety aspects of SC therapy in cardiac patients are discussed.